1979
DOI: 10.1021/j100477a026
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic light scattering of linear polyelectrolyte aqueous salt solutions

Abstract: Publication costs assisted by Centre de Recherches sur les MacromoléculesThe electrophoretic mobility of a synthetic, flexible linear polyelectrolyte (an alternating copolymer of maleic acid and ethyl vinyl ether) dissolved in aqueous solutions of NaBr, under various experimental conditions, was measured by inelastic light scattering. We analyzed the influence of the NaBr concentration, the polyacid concentration, the molecular weight of the poly electrolyte, and the degree of neutralization. The results obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
3

Year Published

1980
1980
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
7
0
3
Order By: Relevance
“…They reported an onset of condensation consistent with Manning's predictions. A similar electrophoretic light‐scattering study by Meullenet, Schmitt, and Drifford of the alternating copolymer of maleic acid and ethyl vinyl ether reached an ambiguous conclusion in regard to Manning condensation 16. In still another study, Cleland found by electrophoresis no evidence for counterion condensation for variably charged polysaccharides 17.…”
Section: Introductionmentioning
confidence: 89%
“…They reported an onset of condensation consistent with Manning's predictions. A similar electrophoretic light‐scattering study by Meullenet, Schmitt, and Drifford of the alternating copolymer of maleic acid and ethyl vinyl ether reached an ambiguous conclusion in regard to Manning condensation 16. In still another study, Cleland found by electrophoresis no evidence for counterion condensation for variably charged polysaccharides 17.…”
Section: Introductionmentioning
confidence: 89%
“…Even the PSS mobility at infinite dilution is not much larger, because the equivalent conductivity, h, of PSS solutions is almost concentration independent (46), in contrast to the sharp increase in A that is commonly observed as polyelectrolytes are diluted (which promotes increased dissociation of counterions) (41). The diffusion coefficients of PSS also differ by only a factor of 2-3 (assuming equal polymer concentrations) over the molecular-weight-range (1-12) X lo5 g/mol (41,44,49) but, unlike the mobilities, depend strongly on polymer concentration (47-49) and added salt (48). Even though the equations for R and H , given earlier assume the good agreement between these equations and thermal FFF experiments (in which the lateral diffusion coefficient varies with temperature) by assigning to D, the diffusion coefficient corresponding to the temperature of the zone's center of gravity (24).…”
Section: Gr = G P a T W 3 / ( P * / P ) 'mentioning
confidence: 99%
“…4 de la réf. [27]), -le PMA (C = 1 g/1) pour des concentrations en NaCI ajouté comprise entre 10-3 et 10-1 M/L (Fig. 7), -l'ADN [4,22], pour les deux échantillons de masses différentes (Fig.…”
Section: Charge Apparente De L'albumine De Sérumunclassified
“…Appl. 16 (1981) [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] 1981, Classification Physics Abstracts 36.20 -61.25 -78.35 -82. 45 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation